This is philosophy an introduction - Hales, Steven D. (This is philosophy, 2021)
"The present book takes a third path. Although it includes commentary on the great historical philosophers and tries to show contemporary relevance, the book introduces students to philosophy topically. While there are references to Buddhism, the Vedas, Islam, and so on, the issues addressed are the bread-and-butter mainstream subjects in broadly analytic Western philosophy. Any student who successfully completes a course based on this book will have a solid grounding in wide variety of topics in different subdisciplines, as well as the pros and cons of different theoretical ways to address those topics. A student who masters the content of this book is well-placed to move on as a philosophy major in the vast majority of philosophy departments. The problems of philosophy are deeply interconnected, and there is no natural or obvious starting point from which to begin. Indeed, plausible arguments might be given for starting with almost any of the central problems in the field. You might think that we should surely start with epistemology; until we understand what knowledge is and settle the matter of whether and how we can gain any knowledge at all, how can we possibly determine whether we can have knowledge of God, or our moral duties, or the nature of the mind? Clearly epistemology is the most fundamental philosophical project. Wait-how can we be sure that knowledge is valuable to have? Or that we ought to care about gaining truth and avoiding error? We'd better start with axiology and sort out duty, obligation, and responsibility first. Normativity and ethics must be foundational. Of course, how can we determine what our epistemic responsibilities are if we don't antecedently know whether we are free to believe one thing rather than another, or if we are truly at liberty to make choices? Let's begin with the issue of free will and figure that out first. If we're not free, that torpedoes a lot of other philosophical agendas. Yet if we don't know what kinds of beings we are, how can we ever determine whether we are free? Maybe personal identity should be the first stop on the road. And so on"--Provided by publisher.